2021
DOI: 10.1242/dev.200080
|View full text |Cite
|
Sign up to set email alerts
|

GAS1 is required for NOTCH-dependent facilitation of SHH signaling in the ventral forebrain neuroepithelium

Abstract: Growth arrest-specific 1 (GAS1) acts as a co-receptor to Patched 1 promoting sonic hedgehog (SHH) signaling in the developing nervous system. GAS1 mutations in humans and animal models result in forebrain and craniofacial malformations, defects ascribed to a function for GAS1 in SHH signaling during early neurulation. Here, we confirm loss of SHH activity in the forebrain neuroepithelium in GAS1-deficient mice and in iPSC-derived cell models of human neuroepithelial differentiation. However, our studies docume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Loss of Notch signalling therefore partially phenocopies loss of SHH. Intriguingly in this regard, recent studies in chick and mouse have suggested that Notch may help to maintain SHH signalling in the spinal cord and rostral ventral forebrain ( Stasiulewicz et al, 2015 ; Marczenke et al, 2021 ). To assist in the interpretation of our results, we therefore asked whether inhibiting Notch would reduce SHH signalling in cultured pHyp explants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of Notch signalling therefore partially phenocopies loss of SHH. Intriguingly in this regard, recent studies in chick and mouse have suggested that Notch may help to maintain SHH signalling in the spinal cord and rostral ventral forebrain ( Stasiulewicz et al, 2015 ; Marczenke et al, 2021 ). To assist in the interpretation of our results, we therefore asked whether inhibiting Notch would reduce SHH signalling in cultured pHyp explants.…”
Section: Resultsmentioning
confidence: 99%
“…SHH and Notch therefore have overlapping but distinct roles in hypothalamic POMC neurogenesis, cooperating to achieve the correct balance between self-renewal and differentiation of progenitors. Mounting evidence suggests that Notch may support SHH signalling in the spinal cord and basal hypothalamus ( Stasiulewicz et al, 2015 ; Marczenke et al, 2021 ), suggesting that some of their common effects may be mediated by signal crosstalk. We now report that Notch signalling is required for PTCH1 expression in cultured hypothalamic explants ( Figures 7A–D ), suggesting that the SHH and Notch pathways synergise to maintain the SOX9+ hypothalamic VZ.…”
Section: Discussionmentioning
confidence: 99%
“…GAS1 functions in several key developmental signaling pathways, including HH, RET, FGF and NOTCH (Allen et al, 2011; Allen et al, 2007; Biau et al, 2013; Cabrera et al, 2006; Izzi et al, 2011; Kann et al, 2015; Li et al, 2019; Lopez-Ramirez et al, 2008; Marczenke et al, 2021; Martinelli and Fan, 2007a; Seppala et al, 2007). GAS1-mediated regulation of these pathways is thought to occur via direct physical interactions between GAS1 and different signaling molecules, including secreted HH ligands and various membrane receptors such as PTCH1, RET, and NOTCH1 (Cabrera et al, 2006; Izzi et al, 2011; Lee et al, 2001; Li et al, 2019; Marczenke et al, 2021). While GAS1 binds HH ligands with high affinity (Huang et al, 2022; Lee et al, 2001), lower affinity interactions have been reported between GAS1 and RET receptors (Cabrera et al, 2006; Li et al, 2019; Rosti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that GAS1 can be secreted in the metanephros, therefore the requirements for GAS1 in a specific pathway (e.g., HH versus RET) could depend on whether it is acting in a cell-autonomous manner (i.e., membrane-tethered) or in a non-cell autonomous fashion (i.e., secreted). GAS1 may also act on multiple signaling pathways simultaneously in a single tissue during development, as suggested for gut development, forebrain development and dentition patterning (Biau et al, 2013; Marczenke et al, 2021; Seppala et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Notch signaling directs HH morphogen activity in the developing ventral spinal cord (Kong et al, 2015). Additionally, the HH co-receptor GAS1 directly binds to NOTCH1 in the developing forebrain, and coordinates HH and Notch signaling in the neuroepithelium (Marczenke et al, 2021). Future studies examining Notch signaling pathway components in our genetic models can elucidate cooperation between HH and Notch signaling in HBCs.…”
Section: Discussionmentioning
confidence: 99%